Anthologies and the Canonization Process:: A Case Study of the English-Canadian Literary Field, 1920-1950 - Kelly, Peggy (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2000)
Editors of anthologies and literary histories have enormous influence not only on the shape and content of their own projects, but also on the shape and content of the traditional curricular canons. However unique and fascinating the 1920 to 1950 time period is, it also resembles other historical moments in Canada through its practice of systemic discrimination on the bases of class, race, sex, and ethnicity. These systemic biases affected the choices made by publishers, editors, and curriculum developers. Their politically based decision-making perpetuated the distinctly Anglo-Saxon, white, and masculine traditional canon that had been developing since the arrival of European settler-invaders. The forty-eight anthologies that make up this study fall into two main groups: anthologies produced by individual editors and anthologies produced by associations. Not only do the academic-professional anthologies include fewer women, they allow even less space to their women writers than is implied by the male-female ratio of their choices. Within this group of English-Canadian anthologies, the ethnicity of Canadian writers is virtually ignored. While nationalist sentiments appear in both association and academic-professional anthologies, internationalism is restricted to the academic-professional group.